Design of a Novel Passive Wireless Integrated SAW-Based Antenna Sensor for Structural Health Monitoring. (13th January 2020) - Dai, Xuan; Fang, Lili; Zhang, Chuanfang; Sun, Houjun
Abstract : A novel passive wireless integrated SAW-based antenna sensor for strain sensing is presented in this paper. A SAW delay line scheme is proposed for signal modulation, which could distinguish the backscattered data from environmental clutter in time domain. The theoretical relationship between the antenna resonance frequency shifts, the temperature, and the applied strain was established. A multiphysical coupled simulation process is proposed to improve the simulation accuracy. By comparing the phase shift of adjacent echoed data which is generated by SAW reflective grating, the temperature information could be extracted exactly and the effect of temperature fluctuation on the resonance frequency could be compensated. A more accurate passive (battery-free) wireless strain sensing could be provided by this proposed integrated antenna sensor than the previous proposed methods. Simulation and experimental results demonstrate the effectiveness of the sensor.